Amphiphilic planar membranes in ionic equilibrium: a study of pH position-dependent values - Bossa, Guilherme V. [UNESP]; Ratero, Davi R. [UNESP]; A. Neto, Augusto [UNESP]; Fahr, Alfred; Souza, Tereza P. [UNESP] (Sociedade Brasileira de Química, 2014)
The pH values near a planar dissociating membrane are studied under a mean field approximation using the Poisson-Boltzmann equation and its linear form. The equations are solved in planar symmetry with the consideration that the charge density on the dissociating membrane surface results from an equilibrium process with the neighboring electrolyte. Results for the membrane dissociation degree are presented as a function of the electrolyte ionic strength and membrane surface charge density. Our calculations indicate that pH values have an appreciable variation within 2 nm from the membrane. It is shown that the dissociation process is enhanced due to the presence of bivalent ions and that pH values acquire better stability than in an electrolyte containing univalent ions.

Os valores de pH na vizinhança de uma membrana ionizável são investigados pelo emprego da equação de Poisson-Boltzmann e de sua forma linearizada. Tais equações são resolvidas para uma simetria plana com a consideração de que a densidade de carga da superfície da membrana resulta de um processo de equilíbrio com a solução eletrolítica. Os resultados para o grau de ionização são apresentados em função da força iônica e da densidade superficial de carga da membrana. Nossos cálculos indicam que os valores de pH possuem uma apreciável variação dentro de uma distância de 2 nm a partir da membrana. É também apresentado que, uma membrana ionizável, na presença de um eletrólito com íons bivalentes, tem seu processo de ionização aumentado pela presença de tais íons. Em tal tipo de eletrólito, os valores de pH são mais estáveis do que em um eletrólito contendo apenas íons monovalentes.
Keywords: pH control; ionic concentration; amphiphilic; Poisson-Boltzmann equation